Cover Image, Volume 117, Number 8, July 1, 2018. Issue 8 (11th September 2018) - Petrovic, Ivana; Rosen, Evan B.; Matros, Evan; Huryn, Joseph M.; Shah, Jatin P.
Abstract : The cover image, by Ivana Petrovic et al., is based on the Review Article Oral rehabilitation of the cancer patient: A formidable challenge, DOI: 10.1002/jso.25075 .